Neuropsychiatric lupus: report of an interesting case with challenges in diagnosis and management - Sharma, Divij; Patel, Varsha; Jagannath, Preethi; Sharma, Saksham (International Journal of Research in Medical Sciences, 2024)
NPSLE, an array of neurological and psychiatric symptoms within systemic lupus erythematosus (SLE), poses diagnostic challenges due to negative serology and absence of systemic signs. We present a 54-year-old woman with anemia, musculoskeletal pain, recurrent pleural effusion, and erratic behavior. Despite delayed identification, extensive testing finally revealed NPSLE. This case underscores the difficulty in linking diverse symptoms to SLE, resulting in delayed treatment initiation and adverse outcomes upon presentation.